Analisis Biaya Riil Dan Kesesuaian Dengan Tarif INA-CBGs Pada Pasien Kanker Ovarium Di RSUD Dr. Moewardi Surakarta Tahun 2018 - Eka Oktafiani (Fakultas Farmasi Universitas Setia Budi, 2020)
Ovarian cancer according to the Indonesian Society of Gynecological Oncology ranks second after cervical cancer. Treatment of ovarian cancer is done by surgery, radiotherapy, and chemotherapy. The study aimed to understand the suitability of real costs with INA-CBG rates and the factors that influence real costs in ovarian cancer patients at hospital Dr. Moewardi Surakarta. The study was taken analytically, the data was taken retrospectively. Subjects were ovarian cancer patients hospitalized at Dr. Moewardi Surakarta in 2018. The analysis used a t-test sample and multivariate analysis to find out research on aid funds with factors related to aid. The results of the study there were 93 patients, 87 patients included in the classification of chemotherapy and 24 patients included in the classification of surgery. Chemotherapy C-4-13-I class 3 has a difference of Rp-2,685,296, in surgery W-1-20-I class 1 the difference is Rp-3,486,814, for class 3 the difference is Rp -6,933,878, W-1 surgery -20-II class 2 the difference is Rp -6,492,889, grade 3 the difference is Rp -20.450.634, and in surgery W-4-10-III class 2 the difference is Rp -13,714,831. The factor that influences the real cost is LOS (Length Of Stay) (p = 0,000) on chemotherapy. The irregular cycle of chemotherapy leads to the cost of chemotherapy for patient ovarian cancer in Dr Moewardi Surakarta 2018.